Dataset of human interventions as anthropogenic perturbations on the Caribbean coast of Colombia (2020)
Human interventions on coastal areas are always causing environmental impact; however, most of the times inventories of those interventions are possibly not well structured, and surely without a specific standard. The raw data presented shows an exhaustive and systematic revision of satellite images on 1700 km of the Caribbean coast of Colombia, where 2743 human interventions were identified. These interventions are classified in 38 categories in order to assess their environmental impact at a regional scale. The filtered data shows the environmental impact obtained for each category and the values allotted to each of the four parameters used for this evaluation. Moreover, the data is filtered for each of the five environmental coastal units in which the Caribbean coast of Colombia is divided by national regulations. Finally, the filtered and processed data shows the analysis done to obtain the graphical results of a previously paper (An evaluation of human interventions in the anthropogenically disturbed Caribbean Coast of Colombia [1]). Therefore, this dataset comprises three spreadsheets (xlsx) and two geographical files (kmz), which are ready to be used for any researcher, decision maker, land planner or practitioner interested in making further analysis on environmental impact assessment in coastal areas. Additionally, the dataset is carefully organised for educational exercises in such a manner that professors or lecturers can repeat the same steps in this study area or in their own, from the inventory to the final results.